Representation of Social Inequality in the Film “Wicked”: Reconfiguring Power Through Fantasy — a Semiotic Reading. - Sherlynn Yuwono; Jandy Edipson Luik; Fanny Lesmana (Petra Christian University, 2025)
This paper explores the representation of social inequality in Wicked (2024), a fantasy musical film directed by Jon M. Chu, using John Fiske’s semiotic approach. Set in the fictional Kingdom of Oz, Wicked offers more than visual spectacle; it is a profound allegory that critiques hegemonic power, class stratification, and systemic marginalization. Through qualitative analysis, this study dissects the film’s signs—costume design, spatial hierarchies, character interactions, and narrative structures—to expose how social disparities are not only depicted but ideologically constructed. Utilizing John Fiske’s semiotic approach, this study aims to uncover how the film, as a subject, conveys objects in the form of signs that reproduce social inequality. The findings reveal that Wicked employs costume design and set aesthetics as semiotic codes to construct the image of hegemony, thereby reinforcing class disparity. Furthermore, the study concludes that the film underscores a critical message: it is not the distinction between right and wrong that determines one’s life trajectory, but rather the possession of power. The unequal access to truth and narrative voice ultimately strengthens the social divide within the film’s storyline—mirroring broader societal realities.